Answer:
Rate of change = -12
Step-by-step explanation:
y − 3 = −12(x + 4)
Expanding, we have;
y - 3 = -12x - 48
y = -12x - 48 + 3
y = -12x - 45
Now, formula for rate of change is;
Rate of change = (y(x + h) - y)/h
y(x + h) is; y = -12(x + h) - 45
This gives;
Rate of change = (-12(x + h) - 45 + 12x + 45)/h
Rate of change = (-12x - 12h - 45 + 12x + 45)/h
Rate of change = -12h/h
Rate of change = -12
Answer: =34
=3⋅3⋅3⋅3
=81
For example, 3 to the power of -4:
=3−4
=134
=13⋅3⋅3⋅3
=181
=0.012346
Step-by-step explanation: the solution is expanded when the base x and exponent n are small enough to fit on the screen. Generally, this feature is available when base x is a positive or negative single digit integer raised to the power of a positive or negative single digit integer. Also, when base x is a positive or negative two digit integer raised to the power of a positive or
negative single digit integer less than 7 and greater than -7.
hopefully this is right :/
Answer:
the answer is d the person above is wrong.
Step-by-step explanation of the wrong answers: b is wrong because it will be 3,3,3,3,3,3,3,4,4,4,5,5,5,6,6. A is wrong because 3 isn't in the middle. C is wrong because then 6-2 is 4. There's your explanation.
<span>The parallel lines extend infinitely in both directions, and the line segment has two endpoints.
</span>
Answer:
yes it is
Step-by-step explanation: